Neighbouring Pixel Matching Pixel Value Differencing Based Image Steganography - Jayeeta Majumder, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Data hiding technique is very significant in the research area of information security. Using different directional way of pixel value comparison, we propose a new Reversible Data Hiding (RDH) scheme. The data extraction process successfully extract secret data as well as recover cover image. Here I observed the efficiency of the proposed method by performing experiments on some standard cover images and found significantly better result in terms of data hiding capacity compared with existing data hiding schemes. To estimate the contrast and smoothness of pixels it also checks the correlation between neighbouring pixels. Edge area pixels tolerate larger changes than the smooth area pixels. The paper considers two, three and four neighbouring pixel matching technique. Through the experimental result it produces the proposed method gives large data hiding capacity with minimum number of distortion.